Cleavage specificities of the brother and sister proteases Lys-C and Lys-N. - Raijmakers, R; Neerincx, P; Mohammed, S; Heck, A (2010)
Understanding of protease specificity is essential in proteomics strategies to correctly compare peptide fragmentation spectra with spectra predicted from data extracted from sequence databases. Here we evaluate the specificities of two proteolytic enzymes Lys-C and Lys-N, which cleave peptide-bonds at, respectively, the C- and N-terminal side of a lysine residue.